ANALISIS PERAN SEKTOR PARIWISATA DALAM PEMULIHAN EKONOMI PASCA PANDEMI COVID-19 DI NTT - Nurani Vita Christiani; Artha Lucya Siahaan (Jurnal Statistika Terapan (ISSN 2807-6214), 2022)
The impact of the Covid-19 pandemic that has hit Indonesia since the beginning of 2020 is felt by all regions and all lines of society. Economic growth in NTT has contracted from the second quarter of 2020 to the first quarter of 2021. Therefore, economic recovery is something that must be a common concern so that the wheels of the economy can return to normal and have a positive effect on all community activities. In this study, we will look at the influence of the tourism sector on economic recovery in NTT. As is known, tourism is the primary sector that is of concern to the NTT’s Regional Government to be able to drive the economy of NTT. The tourism sector in this study was approached with several related industries, namely Land Transport, Sea Transport, ASDP, Air Transport, Accommodation Activities, and Food Service Activities. This study uses Input-Output analysis with the 2016 NTT Input-Output table as the data source. In this Input-Output analysis, structural analysis, linkage analysis (forward linkage and backward linkage), and the resulting impact analysis are also included. The result of this study indicates that the air transport sector is the leading sector based on the index of spreadability and the degree of sensitivity, which is greater than one respectively. The impact of the Output generated due to the effect of final demand is the largest value from the air transport sector.